Anthropological optimism
1 online resource
Keywords: "This book theorizes the role of optimism in anthropological thinking, research, writing, and practice. It sets out to explore optimism's origins and implications, its conceptual and practical value, and its capacity to contribute to contemporary anthropological aims. In an era of extensive ecological disruption and social distress, this volume contemplates how an optimistic anthropology can energize the discipline while also contributing to bettering the lives, communities, and environments of those we study. It brings together scholars diverse in background, career stage, and theoretical approach in a collective attempt to comprehend the myriad intersections of anthropology and optimism. The challenges of the COVID-19 pandemic have recently underscored the larger, longer-term catastrophes of climate change, ecosystemic collapse, social injustice, and antipathy towards scientific knowledge and those who produce it. In this context, exceedingly few anthropologists feel comfortable observing and documenting passively while their research communities face unrelenting waves of (un)natural disasters. We need to act. But we also need to hope. Discontent with the state of the world and cultural anthropology's turn to increasingly positive, future-oriented, and engaged work have converged to unleash a courageously optimistic anthropology. This book is a timely springboard for this impactful and emergent approach"--